PERSEPSI MASYARAKAT TERHADAP PROGRAM SIARAN TAUSHIYAH QOLBU BERSAMA KH. ZAINUDDIN MZ. BERJUDUL HARTA, TAHTA DAN WANITA DI RADIO PRIMA 95.8 FM, HAURGEULIS, INDRAMAYU (Studi pada Masyarakat RT. 15 RW. 05, Blok Buyut, Ds. Haurkolot, Kec. Haurgeulis, Kab. Indramayu) - Mustofa, Mustofa; Fitri, Ahmad Asrof (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
The current era is the Information Age. Information has become the most important "commodity of life" for people to get information, education, entertainment, business, da'wah and others. One of them through Radio Electronic Media. Dakwah broadcasts via radio are also a concern and evaluation by the public in the form of perceptions and the factors that influence them. This thesis examines the perception of the audience/listeners (Community of RT. 15 RW. 05 Buyut Block, Haurkolot Village, Haurgeulis District, Indramayu Regency) and the factors that influence it towards the Taushiyah Qolbu Broadcast Program with KH. Zainuddin MZ. Titled Wealth, Throne and Women on Radio Prima 95.8 FM Haurgeulis, Indramayu. The research method used is a qualitative descriptive method, field research which is described using in-depth words and language (not statistics/numbers) obtained by collecting data through observation, interviews and documentation. The results of this research describe the perceptions (views/impressions) of the audience/listeners (society) of 20 people who were the research objects, namely (1) Positive assessment of the da'wah format broadcast program, namely Taushiyah Qolbu with material on Treasure, Throne and Women. They feel that there are many benefits, adding knowledge and insight into Islam, they feel comfortable and try to practice it in their daily lives. (2) Their perception is influenced by a). Factor attention (attention). b). Attention-grabbing external factors. c). Internal factors influence attention. d). Functional Factors. e). Structural Factors. These five factors influence each individual's perception (view/impression) based on life experience, situations and conditions, according to their interests and needs.